Challenges of Health Technology Incubators in Iran: A Qualitative Study - Mohammad Ali Moghbeli; Ali Reza Kalantari; Somayeh Noori Hekmat; Mahshid Salemian pour; Ehsan Lorafshar; Mohammad Saleh Koushki; Reza Dehnavieh (Shahid Sadoughi University of Medical Sciences, 2019)
Background: Health Technology Incubators (HTI) play an important role in paving the way depicted in Iran's comprehensive health plan in order to achieve the aimed position in 2025. In light of the emerging nature of these centers in Iran, identification of HTI problems and challenges, as well as appropriate planning to resolve those problems can have a significant effect and improve Iran's health system functionality. Methods: This qualitative study was conducted in Iran in 2016. Data were collected through interviews with 24 experts (Interviewees included managers, deputies, and employees from the country's incubators) in the field. Purposeful sampling continued until data saturation level was achieved. All interviews were recorded and then analyzed, and main themes and subgroups were extracted from them based on a framework analysis. In all the mentioned steps the Atlas-Ti software has been employed. Results: Challenges of Health Technology Incubators in Iran were categorized into eight concepts- Cultural,   Rules and Principles, Funding, Concentrated Administrative System, Human Resources, Stewardship and Monitoring, Physical space and Equipment, and Communicational. Then 22 challenges were identified with in these concepts. Conclusion: This study suggests that considering the challenges influencing technology incubators in the health sector, a sustainable program for these centers can be designed.